Toward Sustainable HPC: In-Production Deployment of Incentive-Based Power Efficiency Mechanism on the Fugaku Supercomputer - Solorzano, Ana Luisa Veroneze; Sato, Kento; Yamamoto, Keiji; Shoji, Fumiyoshi; Brandt, Jim M.; Schwaller, Benjamin; Walton, Sara Petra; Green, Jennifer; Tiwari, Devesh (SC24: International Conference for High Performance Computing, Networking, Storage and Analysis, 2024)
This paper describes the deployment and operational experience of a novel incentive-based power-control strategy on the Fugaku supercomputer. Our incentive-based program, termed Fugaku Points, provides knobs to users to apply power control functions to improve the overall power efficiency of the supercomputer toward achieving HPC sustainability in terms of its environmental implications. We also discuss new operational opportunities, challenges, and future directions.